TANTANGAN IMPLEMENTASI HUKUM KELUARGA DI INDIA: PENCATATAN PERNIKAHAN DAN PERLINDUNGAN HAK PEREMPUAN - Napisah, Napisah; Huzaimah, Huzaimah (MAQASHIDUNA: JURNAL HUKUM KELUARGA ISLAM, 2025)
Abstract:The implementation of family law in India faces complex challenges due to legal pluralism and deep-rooted patriarchal social norms, especially in the Muslim community. Although formal laws such as the Prohibition of Child Marriage Act and the Special Marriage Act have regulated the age limit for marriage and the mechanism for registration, the practice of child marriage and unregistered marriages are still widespread. The purpose of this study is to determine how family law is implemented, how the practice of registering marriages takes place, and how the age limit for marriage is implemented in India, especially in the Muslim community. This study uses a juridical-normative approach with a qualitative descriptive-analytical method, through a literature study of Islamic legal sources and Indian legislation. The results of the study show three main findings: (1) the inconsistency between normative Islamic law and social practices in guaranteeing women's rights; (2) the weakness of the Muslim marriage registration system which has an impact on women's legal vulnerability; and (3) the gap between the regulation of the age limit for marriage and the practice of early marriage influenced by social and religious norms. This study emphasizes the importance of a holistic approach in family law reform in India.Keywords: Family Law, Muslims in India, Marriage Registration, Protection of Women's RightsAbstrak:Penerapan hukum keluarga di India menghadapi tantangan kompleks akibat pluralisme hukum dan norma sosial patriarkal yang mengakar, khususnya dalam komunitas Muslim. Meskipun hukum formal seperti Prohibition of Child Marriage Act dan Special Marriage Act telah mengatur batas usia perkawinan dan mekanisme pencatatan, praktik pernikahan anak dan tidak tercatatnya perkawinan masih marak terjadi. Tujuan penelitian ini adalah untuk mengetahui bagaimana hukum keluarga diterapkan, bagaimana praktik pencatatan perkawinan berlangsung, serta bagaimana batas usia perkawinan dijalankan di India, khususnya dalam komunitas Muslim. Penelitian ini menggunakan pendekatan yuridis-normatif dengan metode kualitatif deskriptif-analitis, melalui studi pustaka terhadap sumber hukum Islam dan peraturan perundang-undangan India. Hasil penelitian menunjukkan tiga temuan utama: (1) ketidaksesuaian antara hukum Islam normatif dan praktik sosial dalam menjamin hak-hak perempuan; (2) lemahnya sistem pencatatan perkawinan Muslim yang berdampak pada kerentanan hukum perempuan; dan (3) kesenjangan antara regulasi batas usia menikah dan praktik pernikahan dini yang dipengaruhi norma sosial dan keagamaan. Kajian ini menegaskan pentingnya pendekatan holistik dalam reformasi hukum keluarga di India.Kata Kunci: Hukum Keluarga, Muslim di India, Pencatatan Pernikahan, perlindungan Hak Perempuan.